Decay Kinetics of HIV-1 Specific T Cell Responses in Vertically HIV-1 Exposed Seronegative Infants - Holditch, Sara J.; Eriksson, Emily M.; Tarosso, Leandro F.; Kuebler, Peter J.; Kallas, Esper G.; Nielsen, Erik K.; Wiznia, Andrew A.; Rosenberg, Michael G.; Nixon, Douglas F. (Frontiers in Immunology, 2012)
The majority of infants born to HIV-1 positive women are exposed to the HIV-1 virus in utero or peri/post-partum, but are born uninfected. We, and others, have previously shown HIV-1 specific T cell responses in HIV-1 Exposed Seronegative (HESN) neonates/infants. Our objective in this study was to examine the rate of decay in their HIV-1 specific T cell response over time from birth. Cross-sectional and longitudinal studies of HIV-1 specific T cell responses in HIV-1 Exposed Seronegative (HESN) infants were performed. Peripheral blood mononuclear cells (PBMC) were isolated from eighteen HIV-1 DNA PCR negative infants born to HIV-1 infected mothers receiving care at the Jacobi Medical Center, Bronx, NY. PBMC were examined for T-cell responses to HIV-1 antigens by interferon gamma (IFN-) ELISPOT. We observed a decay of HIV-1 specific T-cell responses from birth at a rate of -0.599 SFU/106 cells per day, with a median half-life decay rate of 21.38 weeks (13.39-115.8). Our results support the dynamic nature of T cell immunity in the context of a developing immune system, and suggests that antigen specific T cell responses are driven by the natural rate of decay of the T cell subpopulations themselves.